Trapped in folklore? : studies in music and dance tradition and their contemporary transformations - Kunej, Drago; Šivic, Urša (Musikethnologie, 2013)
Questions like 'Trapped in folklore?' open up many possibilities for reflection and prompt different answers. This thematic publication with a rather provocative title discusses questions as to whether the selected musical phenomena are a fossilised form of tradition, folklore and folklorism and, as such, are trapped in a museum-like image isolated from contemporary cultural life, or whether we are looking at active events, changes, and adjustments within contemporary society.
Keywords: Folk music : History and criticism : Congresses; Music and folklore : Congresses; akkulturaatio; arkistot; digitointi; etnomusikologia; folklorismi; kansanmusiikki; kansanperinne; kansansoittajat; kansantanssit; kyläyhteisöt; modernisaatio; musiikki; musiikkikulttuuri; naiset; nostalgia; performanssi; puhallinorkesterit; säkkipilli; tanssipaikat; äänitteet; ackulturation; arkiv; digitalisering (verksamhet); etnomusikologi; folklorism; folkmusik; folktradition; spelmän; folkdanser; bysamhällen; modernisering; musik; musikkultur; kvinnor; nostalgi; performance; blåsorkestrar; säckpipa; dansställen; ljudupptagningar (produkter); Balkanin niemimaa; Kosovo; Kroatia; Montenegro; Romania; Serbia; Slovenia; Unkari; Vojvodina; Balkanhalvön; Kroatien; Rumänien; Serbien; Slovenien; Ungern; călus; etnokoreologia; revena; táncház